Reviving Businesses With New Organizational Change Management Strategies - Geada, N.; Anunciação, P (2021)
With the gradual resumption of economic activity, most businesses are facing a range of challenges associated with implementing measures to protect the health and safety of their employees. Some employers had to put certain business activities on hold and even start new ones in order to keep their organizations operating efficiently. The global COVID-19 pandemic plus digital transformation and the pressure of Industry 4.0 have challenged companies to manage their organizations in newfound ways. In the short term, they are facing enormous changes to their business plans; in the long term, they must adapt and continue to progress on their original goals. Reviving Businesses With New Organizational Change Management Strategies is a crucial reference book that analyzes the sensitivity of organizations to change management based on methodologies and tools to control impacts, to understand how employees will be impacted in their environment, and to learn how technology will help both the industry and professionals. This book also explores types of frameworks that are built for communication and business continuity, the importance of collaborative and interactive relationships for change management, and emotional factors and issues for change management. Covering topics including change management models, cybersecurity, Health 4.0, privacy and security, and information systems management, this text is essential for managers, executives, human resources managers, academicians, students, and researchers looking for successful business strategies that are leading to increased efficiency, performance, and growth.